Students' Response toward Facebook as a Media in Learning Bahasa Indonesia - Lira Hayu Afdetis Mana (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
A tedious situasion of learning Bahasa Indonesia in this pandemic era makes Facebook become a choice to have a varied and interesting learning process. Therefore, it is necessary to conduct a research on the students` responses toward Facebook as a medium of learning. This is a descriptive qualitative research. The instrument used in this research was students` response questionnaires to Facebook as a learning medium which was distributed to 145 high school students in West Sumatera by using the google form. The link was distributed through the Whatsapp Group. The results of this study shows that students : [1] are familiar with, have downloaded and used Facebook; [2] saw Facebook as a positive, profitable and entertaining application; [3] (minority) saw Facebook as a negative, harmful, and unsatisfactory application; [4] like Facebook because they can get information; [5] mostly agree that the Facebook application is used as a medium for learning Bahasa Indonesia (listening, speaking, reading, and writing); [6] (minority) do not like to use Facebook due to many naughty and fraudulent accounts appear; [7] (mostly) have received information on procedural texts, short stories or narrative texts, explanatory texts, observation report texts, exposition texts, anecdotal texts, poetry texts and negotiation texts. Then, [8] a small proportion of students have never seen debates, saga, novels, dramas, lectures. Hence, it can be concluded that Facebook can be used as a learning medium to make the students motivated and enjoyed the learning process.